Pigment fingerprint profile during extractive fermentation with Monascus anka GIM 3.592 - Kan Shi; Rui Tang; Tao Huang; Lu Wang; Zhenqiang Wu (BMC Biotechnology, 2017)
Abstract Background Traditional submerged fermentation mainly accumulates intracellular orange pigments with absorption maxima at 470 nm, whereas extractive fermentation of Monascus spp. with Triton X-100 can promote the export of intracellular pigments to extracellular broth, mainly obtaining extracellular yellow pigments with absorption maxima at approximately 410 nm. In this study, a strain of Monascus (M. anka GIM 3.592) that produces high yields of pigments was employed to investigate the differences in pigment fingerprint profiles between submerged and extractive fermentations. Results Using extractive fermentation with this high-yield strain, the extracellular pigments exhibited an absorption maximum at 430 nm, not 410 nm, as previously observed. By comparing the pigment fingerprint profiles between submerged and extractive fermentations, extractive fermentation was found to not only export intracellular pigments to the extracellular broth, but also to form four other yellow pigments (Y1-Y4) that accounted for a large proportion of the extracellular pigments and that were not produced in submerged fermentation. The yields of Y1-Y4 were closely related to the concentration and feeding time point of Triton X-100. Y1-Y4 presented identical UV-Vis spectra with absorption maxima at 430 nm and fluorescence spectra with absorption maxima (emission) at 565 nm. HPLC-MS and the spectral analysis showed that the four pigments (Y1-Y4) had not been previously reported. The results indicated that these pigments may rely on the bioconversion of orange pigments (rubropunctatin and monascorubrin). Conclusions Using extractive fermentation with M. anka led to a high yield of extracellular yellow pigments (AU410 nm = 114), and the pigment fingerprint profile significantly differed compared to the results of traditional submerged fermentation. These results provide information and a detailed view of the composition and variation of pigments in extractive fermentation and could also contribute to characterizing pigment metabolism during extractive fermentation.